Pengaruh Periklanan Terhadap Keputusan Pembelian Konsumen Pada PT. Astra International Daihatsu - Surandy Malunsenge; Lucky F Tamengkel; Aneke Y. Punuindoong (JURNAL ADMINISTRASI BISNIS, 2017)
This research is based on thinking on several factors that influence consumers to buy in car dealers. With the growing efforts of the automotive industry today the level of competition among automotive industry is increasingly competitive, each dealer has a strategy in persuading the customers to choose and / or buy a car. Due to the innovation of marketing strategy changes and from the supporting factors such as; give Attention, desire analysis, ad image, techniques to increase attractiveness. And interesting advertising support will make consumers take a decision in buying at Astra international (Daihatsu). This activity was held at PT. Astra International Daihatsu branch Manado in order to know the relationship of these factors affect consumers to buy. Besides, this research is expected to be input to the leadership of PT. Astra International Manado and is a contribution in marketing and advertising strategy. Data collection using the instrument in the form of questionnaires / interviews, observation and document studies, and for data analysis using quantitative methods. The results of this study to answer the hypothesis there is a significant relationship factors that influence consumers to buy, with a determinant indicates 49.92% which means that the increase or decrease in customer savings depends on those factors are strong enough 0.7066%, the remaining 50.08% is another factor. Positive linear functional relationships of 1: 0.7378 scale means the increase in advertising will affect the increased purchase decision of 0.7378Keyword : Advertising, Costumer Decision